Effects of hydrothermal annealing on characteristics of CuInS 2 thin films by SILAR method - Shi, Y.; Xue, F.; Li, C.; Zhao, Q.; Qu, Z.; Li, Xin Yong (2012)
CuInS2 thin films have been deposited by successive ionic layer absorption and reaction (SILAR) method, then annealed in a Na2S solution (denoted as hydrothermal annealing) at 200 °C for different time. The effect of hydrothermal annealing on the properties of the films was studied by X-ray diffraction (XRD), scanning electron microscopy (SEM), X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM) and optical absorption spectroscopy. The XRD, TEM and SEM results indicate that well-crystallized CuInS2 films could be obtained after annealing in 0.1 mol/L Na2S solution for 1.5 h. The annealed CuInS2 films were slightly S-rich and the direct band gap varied from 1.32 to 1.58 eV as the annealing time increased from 0.5 h to 2 h.